Carotid angioplasty-assisted mechanical thrombectomy without urgent stenting may be a better option in acute tandem occlusions - Akpinar, Cetin K.; Gurkas, Erdem; Aytac, Emrah (Sage Publications Inc, 2017)
Background: The aim of the study was to assess the efficacy of balloon angioplasty-assisted mechanical thrombectomy without urgent stenting in the carotid artery as another approach for endovascular treatment of tandem occlusions. Methods: Fifteen consecutive cases of tandem occlusions treated with the endovascular approach between January 2014 and May 2016 were reviewed. The study cohort included patients with an etiology of large vessel atherosclerosis. Extracranial carotid stenting was performed in another session if post-thrombectomy mRS modified Rankin Score (mRS) was 0-2. Good clinical outcome was determined by follow-up at 7-10, 30 and 90 days according to the mRS. Results: Most patients (80%) were male. Eight (53.4%) patients received intravenous thrombolysis before angiography. Proximal revascularization was successful in 100% of cases with balloon angioplasty internal carotid artery (ICA) origin. Successful recanalization (modified thrombolysis in cerebral infarction (mTICI) 2b-3) (mTICI 2b-3) occurred in 12 cases (80%) and good clinical outcomes were achieved in 10 patients (66.7%). Cervical ICA stent placement was performed in 10 patients with good clinical outcomes. No symptomatic intracranial hemorrhage occurred after delayed ICA stenting Conclusions: This is the first reported case series to evaluate this approach for endovascular treatment of tandem occlusions. Carotid angioplasty-assisted mechanical thrombectomy without urgent stenting seems to be a safer approach.
Keywords: Acute stroke; angioplasty-assisted mechanical thrombectomy; carotid angioplasty; interventional neurology; tandem occlusion